ELECTRONIC RESOURCES IN TEACHING AND LEARNING THE HISTORY OF PEDAGOGY - Кірдан, Олена Леонідівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The research on the problem of using electronic resources in teaching and learning the history of pedagogy is relevant at theoretical, methodological and practical levels. Some of its aspects were considered in the works of domestic scientists on the organization of blended learning, the use of electronic learning tools, didactic opportunities of open educational resources, etc. On the basis of the analysis of legal documents, state standards of higher pedagogical education, own practical activity, it was ascertained on the necessity to use the potential of electronic resources in teaching and teaching the discipline «History of Pedagogy». The purpose is to identify and analyze electronic resources as a component of sources of information in teaching and teaching of the educational component «History of Pedagogy» in higher education institutions of Ukraine. The following methods were used to achieve the defined goal and tasks: theoretical: analysis, synthesis, concretization, comparison and generalization of scientific sources of the circle of the studied problem; study of regulatory documents; empirical: analysis and generalization of pedagogical experience. According to the information criterion, the following groups of electronic resources – components of the recommended sources of information in teaching and teaching of the educational component «History of pedagogy» are identified and characterized: electronic resources of local networks; open educational resources; electronic documents; digital resources; scientific information databases; electronic libraries, historical and cultural resources; electronic biographies; electronic collections; historical and pedagogical sites and museum sites. The peculiarities of the content filling of isolated groups of electronic resources are revealed. The topics of the educational component «History of the Ukrainian School and Pedagogy» are specified, the contents of which are recommended for updating on the basis of the offered electronic resources